The Influence of Breakfast Habits on the Learning Concentration of Culinary Class Students at SMK Negeri 2 Pariaman - Suci Rahmadhani; Kasmita Kasmita; Yuliana Yuliana; Lucy Fridayati (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
The lack of student learning concentration that interferes with learning at SMK Negeri 2 Pariaman is a problem that needs to be overcome. Based on observations, students who do not eat breakfast tend to arrive late, often sleepy, and some even faint due to poor health conditions. Breakfast is the best source of energy for concentration because it contributes 25% of daily energy needs. This study aims to determine the breakfast habits of culinary students, the level of study concentration, and analyze the influence of breakfast habits on students' learning concentration. The research uses a quantitative method with an ex post facto approach. The research population is all students Culinary SMK Negeri 2 Pariaman totaling 126 students using the total population technique. Data were collected through a Likert scale questionnaire and analyzed using descriptive statistics, normality tests, linearity tests, and Pearson Product Moment correlations. The breakfast habits of students with an average of 64.05 are in the medium category, while learning concentration with an average of 70.60 is in the high category. There was a significant positive relationship between breakfast habits and study concentration (r = 0.437; p < 0.05). Breakfast habits contributed 19.1% to student learning concentration. There is a positive and significant influence between breakfast habits on the learning concentration of culinary students at SMK Negeri 2 Pariaman. The better the breakfast habits, the higher the student's level of study concentration.